2022
DOI: 10.1007/s00246-022-02956-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Right Ventricle to Pulmonary Artery Biologic Valved Conduits Used in Pediatric Congenital Heart Surgery

Abstract: Valved conduit reconstruction between the right ventricle (RV) and the pulmonary circulation is often necessary in the surgical treatment of complex congenital heart defects. The aim of this study is to evaluate the long-term performance of the three types of conduits we have used and assess risk factors for conduit failure. Retrospective, single-center review of 455 consecutive pediatric patients with 625 conduits from 1990 to 2019 undergoing RV-to-pulmonary artery (PA) reconstruction with a valved conduit. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Clearly, in this setting, one has to remind that the patients are older when they receive their second graft. The results are also consistent with Lewis et al, which demonstrated no evidence for a shorter life span of the second graft (Lewis et al 2023 ).…”
Section: Discussionsupporting
confidence: 91%
“…Clearly, in this setting, one has to remind that the patients are older when they receive their second graft. The results are also consistent with Lewis et al, which demonstrated no evidence for a shorter life span of the second graft (Lewis et al 2023 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although the conclusions of material influence were inconsistent, most studies confirmed that the durability of PHG was significantly longer than those of xenograft and AHG. Besides, many studies found small conduit size, young age, and low-weight of the patient to be risk factors for conduit failure [7,8,10,11]. In our opinion, although these were reasonable risk factors for conduit stenosis, they cannot fully explain the mechanism underlying stenosis progress.…”
Section: Mechanism Of Conduit Stenosismentioning
confidence: 69%
“…We combined the AHGs and PHGs into Homografts for baseline data and multivariate analysis. However, in some previous large sample studies, the durability of AHGs was worse than that of PHGs [810]. Therefore, we hypothesized that the PM 2.5 effect on their durability was different.…”
Section: Resultsmentioning
confidence: 89%
“…Recently there is an increasing number of alternative valved conduits implanted, such as BJVC. In fact, there are centers reporting either the superiority (7) or equivalence (13,8) of BJVC to homografts.…”
Section: Discussionmentioning
confidence: 99%